Efektivitas Kecerdasan Emosional : dalam Peningkatan Komitmen Organisasi dan Kepuasan Kerja Karyawan - Vionaliza Okta Rahmadiyanti; Mudji Kuswinarno (Ebisnis Manajemen, 2024)
This research analyzes the role of emotional intelligence in enhancing organizational commitment and employee job satisfaction. Emotional intelligence, which includes the ability to manage one's own emotions and understand the emotions of others, has been shown to improve interpersonal relationships, reduce work-related stress, and strengthen employee commitment to the organization. The methodology employed is a literature review, with data gathered from relevant journals and books. The findings indicate that emotional intelligence significantly contributes to increased job satisfaction and organizational commitment, which, in turn, positively influences employee performance. This study suggests that organizations should implement emotional intelligence training programs to foster a supportive work environment that promotes employees' emotional well-being and enhances overall performance.